2017
DOI: 10.1002/jbt.21940
|View full text |Cite
|
Sign up to set email alerts
|

Alpha lipoic acid prevents doxorubicin-induced nephrotoxicity by mitigation of oxidative stress, inflammation, and apoptosis in rats

Abstract: This study aimed to evaluate the protective effects of alpha lipoic acid (ALA) against doxorubicin (DOX)-induced nephrotoxicity in rats. A single dose of DOX (7.5 mg/kg i.v.) induced nephrotoxicity evidenced by significant elevations in kidney weight, kidney/body weight ratio, serum urea, creatinine, tumor necrosis factor alpha, and renal contents of malondialdehyde, nitric oxide, cyclooxygenase-2, and caspase-3. Also, it causes significant reduction in final body weight, serum albumin, renal contents of reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 57 publications
2
18
1
Order By: Relevance
“…Being both administrations toxic, (−) enantiomer appeared to be the responsible for the results induced by racemic mixture. In literature we found voices opposing to our results: some studies reported an antiapoptotic activity of thioctic acid, when the dietary supplement was administered orally and at lower concentration (50 mg/kg) [ 29 , 30 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Being both administrations toxic, (−) enantiomer appeared to be the responsible for the results induced by racemic mixture. In literature we found voices opposing to our results: some studies reported an antiapoptotic activity of thioctic acid, when the dietary supplement was administered orally and at lower concentration (50 mg/kg) [ 29 , 30 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Researchers demonstrated that elevation of apoptosis-related protein like BAX, caspase-3 and cytochrome c in DOX-intoxicated rats might be contributed to renal dysfunction. 54,58 By activating caspase-3 in renal proximal tubular cells and causing mitochondrial pathway, DOX probably leads apoptosis, which can arise renal cell damage and disorganized renal histology. 59 In present study, under the pretreatment of YQFM, expressions of BAX/Bcl-2 ratio, caspase-3 and cytochrome c were quite reduced, and then the inhibition of apoptosis could prevent tissue lesions and dysfunction, which was associated to the effect of ginsenosides included in YQFM.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that proteinuria is caused by glomerulosclerosis and loss of glomerular podocytes due to cell death/apoptosis [ 1 ]. Results from previous studies have demonstrated that oxidative stress, inflammation, and apoptosis are involved in the development of NS pathological features [ 2 ]. In the patients without effective treatment, NS leads to end-stage renal disease (ESRD) and require renal transplantation [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advances in NS studies in recent decades, the pathophysiology of this disease remains unknown and more studies are needed to clarify its exact pathophysiological mechanisms. Adriamycin (ADR) is a common anticancer drug that has been used for the treatment of a wide range of human solid tumors since 1969 [ 2 ]. However, despite having high antitumor efficacy, its effectiveness has been limited, because of renal, myocardia, testicular, and hematological toxicities [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation